Sex Differences in the White Matter and Myelinated Fibers of APP/PS1 Mice and the Effects of Running Exercise on the Sex Differences of AD Mice - Zhou, Chun-ni; Chao, Feng-lei; Zhang, Yi; Jiang, Lin; Zhang, Lei; Luo, Yan-min; Xiao, Qian; Chen, Lin-mu; Tang, Yong (Frontiers in Aging Neuroscience, 2018)
Previous studies have suggested that changes in the white matter might play an important role in the pathogenic processes of Alzheimer's disease (AD). However, no study has investigated sex differences in these changes. Previous studies found that running exercise could delay both the decline in spatial learning and memory abilities as well as the changes in the white matter during early AD in male mice. However, whether exercise also has an effect on the changes in the white matter in female AD mice remains unknown. To address these questions, 6- and 10-month-old male and female APP/PS1 double transgenic AD mice were used. The 6-month-old male and female APP/PS1 double transgenic AD mice underwent a 4-month running exercise regime. The white matter volume and parameters of the myelinated fibers in the white matter of the 10-month-old exercised and non-exercised male and female AD mice were investigated using electron microscopy and stereological methods. There were no significant differences in the mean escape latencies between the male and female AD mice in the non-exercised groups, but after 4 months of treadmill exercise, the mean escape latencies of the female exercised AD mice had significantly shortened compared with those of the male exercised AD mice. The total white matter volume and most of the parameters of the myelinated fibers of the white matter in the female AD mice were significantly lower than those of the male AD mice. The total length of the myelinated fibers with diameters ranging from 0.6 to 0.7 μm, the axonal diameter of the myelinated fibers and the g-ratio of the myelinated fibers in the white matter of the exercised female AD mice were significantly increased compared with those of the non-exercised female AD mice. There were sex-specific differences in the white matter and myelinated fibers of white matter in the AD mice. Running exercise more effectively delayed the decline in spatial learning and memory abilities and delayed the changes in the myelinated fibers of the white matter in female transgenic mice with early AD than in male transgenic mice.